Preferensi Masyarakat Terhadap Quick Response Code Indonesian Standard Sebagai Sarana Teknologi Pembayaran Digital - Rina Mayanti (Faktor Exacta, 2022)
The development of electronic money transactions have grown rapidly especially in the digital payment sector. This study aims to analyze the acceptance factors of user intentions in the application of the Quick Response Indonesia Standard as an electronic wallet payment technology. The user acceptance regarding the Quick Response Indonesia Standard  implementation is predicted by user technology acceptance model Unified Theory of Acceptance and Use Technology 2. The object of this study is the Shopeepay and OVO digital wallet user who is domiciled in Jakarta. Data collection techniques by google forms. The independent variables used in this research are all Unified Theory of Acceptance and Use Technology2 model variables except age, gender, experience, and price value using Partial Least Squares-Structural Equation Modelling analysis techniques. The result of this  syudy indicate that the facilitating conditions and hedonic motivation affect the user's behavioral intention for using QRIS as their payment technology, and behavioral intention also gives the effect to their use behavior.